Where to next?: Logistics system – Pimensor - Duarte, Carolina Silvério Carvalho (2023)
This study is based on a Portuguese SME that is Pimensor, a company based in Alentejo that produces agri-food products used in traditional Portuguese cuisine, it has the intention of developing a logistics and supply chain strategy in order to help the company expand to a new market, the objective is to provide a new insight and analysis of Pimensor, as well as, give suggestions, based on the analysis made, so that this company can expand without compromising the logistics and supply chain of the company and the services already existent. The strategy that is going to be used has to be appropriated and customized for the company and the possible new market since not all markets are the same, neither are the goals of the company to each market. This thesis has some limitations since it is a specific food related product with conditions and characteristics of its own. To research and analyze this topic, it was conducted a case study with data collected during the internship.